2020
DOI: 10.1002/bbb.2138
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost and sustainable (nano)catalysts derived from bone waste: catalytic applications and biofuels production

Abstract: The application of (bio)wastes as alternatives to expensive existing catalysts is an approach that can be used to reduce environmental pollution problems. Animal bone wastes have attracted much attention as environmentally friendly heterogeneous catalysts for chemical transformations such as transesterification, oxidation, and biofuel production, owing to the substantial availability of valuable hydroxyapatite (HAp) in their structure. Most catalysts based on bone can be prepared easily by calcination. High-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 150 publications
(200 reference statements)
0
16
0
Order By: Relevance
“…Various efforts have been put to convert potent functional ingredients into novel formulated foods. To control this immense waste, its transformation into valuable and incredible materials could prove the best choice (Nasrollahzadeh et al., 2020). From nutritional point of view, these bones’ waste is intended to be recycled and used in fabrication of bone grafting and minimising risk of osteopenia development at early ages (Tram et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Various efforts have been put to convert potent functional ingredients into novel formulated foods. To control this immense waste, its transformation into valuable and incredible materials could prove the best choice (Nasrollahzadeh et al., 2020). From nutritional point of view, these bones’ waste is intended to be recycled and used in fabrication of bone grafting and minimising risk of osteopenia development at early ages (Tram et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…11,41,42 Other applications of this material include bioceramics, adsorbents, catalyst and catalyst support, powder carriers, chromatographic lighting materials, and chemical sensors. 21 The molecular structure of the calcium apatite [Ca 10 (PO 4 ) 6 (OH) 2 ] is shown in Fig. 3.…”
Section: àmentioning
confidence: 99%
“…However, for bone materials, the analogous Ca/P value is in the range of 1.37-1.87 because of the presence of other ions such as zinc, magnesium carbonate, and silicon. 21 Processing conditions affect a wide variety of properties of the produced HA material, including the Ca/P ratio, crystal structure, particle shape, particle size, and biological properties, 43,48 which can be studied using methods such as X-ray diffraction, scanning electron microscopy, transmission electron microscopy, thermogravimetric analysis and differential thermal analysis, and bioactivity and biocompatibility techniques. It has been reported that calcining acid-treated chicken bones at 900 C produced crystalline HA particles of size 600 nm and pore morphology of 208 nm, with Ca/P atomic ratios of 1.653 and high thermal stability, suitable for biomedical applications.…”
Section: àmentioning
confidence: 99%
“…S1(a)) depicts the main functional groups present in the material. The wide bands from 3787 to 3445 cm −1 are commonly assigned to the stretching vibrations of O━H typical of water molecules , 31 The bands at 2399 and 1573 cm −1 are attributed to the stretching vibrations of M━O━K bonds (M〓Si, Mg). 6 The peak at 1335 cm −1 is associated with K 2 CO 3 produced by the adsorption of atmospheric CO 2 onto metal oxides.…”
Section: Characterization Of Tpc7mentioning
confidence: 99%